Acute Osteomyelitis in the Hand Due to Dog Bite Injury: A Report of 3 Cases - Ryun Lee (Archives of Plastic Surgery, 2017)
As many people keep small dogs as pets, dog bites are common injuries, accounting for approximately 80%–90% of all animal bite injuries. These injuries usually occur on the upper extremities, most commonly on the fingers. Most of these injuries appear as simple lacerations or abrasions of the skin. Common symptoms include inflammatory reactions of the soft tissue, such as pain, swelling, erythema, and cellulitis. However, the complications of small dog bites may include joint or cartilage injuries, including acute osteomyelitis. Once osteomyelitis develops, it is difficult to diagnose since it has a latency period of approximately 2 weeks. Plain radiography, magnetic resonance imaging, and 3-phase bone scans should be performed when acute osteomyelitis is suspected, and broad-spectrum empiric antibiotic treatment should be administered for approximately 8–12 weeks. We report 3 very rare cases of acute osteomyelitis that occurred after a dog bite injury.